Compressible flows on moving domains: Stabilized methods, weakly enforced essential boundary conditions, sliding interfaces, and application to gas-turbine modeling. (24th November 2017) - Xu, Fei; Moutsanidis, George; Kamensky, David; Hsu, Ming-Chen; Murugan, Muthuvel; Ghoshal, Anindya; Bazilevs, Yuri
Highlights: A novel stabilized formulation for compressible flows on moving domains using the ALE approach is proposed. A direct approach to the construction of the stabilization matrix, which consistently accounts for the stabilization of all the modes in the compressible-flow equations system, is developed. A new formulation for weakly enforced essential boundary conditions is proposed. A new formulation for sliding interfaces is proposed. Abstract: A novel stabilized formulation for 3D compressible viscous flows on moving domains is developed. New weak imposition of essential boundary conditions and sliding-interface formulations are also proposed in the context of moving-domain compressible flows. The new formulation is successfully tested on a set of examples spanning a wide range of Reynolds and Mach numbers showing its superior robustness. Experimental validation of the new formulation is also carried out with good success. In addition, the formulation is applied to simulate flow inside a gas turbine stage, illustrating its potential to support design of real engineering systems through high-fidelity aerodynamic analysis.